Isolation, selection and evaluation of α-glucosidase inhibitory activity from endophytic Streptomyces sp. isolated from Citrus myrtifolia cultivar in Hoa Binh, Vietnam - Thi Trung, Nguyen; Thi Thao, Nguyen; Hong Thao, Phan Thi; Thanh Tuan, Tran; Duy Nam, Pham; Thanh Hoang, Le; Tuyen, Do Thi (Vietnam Journal of Biotechnology, 2022)
Cao Phong orange (Citrus sinensis Lour) was grown in Cao Phong district, Hoa Binh province. Citrus sinensis is Vietnam’s most valued commercial fruit. In this study, 30 microorganim strains were isolated from the samples of root, stem, and leaf of Cao Phong orange. The ratio of endophytic actinomycetes was found in different parts of the plant: root, stem, and leaf was 37%, 40%, and 23%, respectively. The isolating HBC6-2 was selected because of its high output of α-glucosidase inhibitors from 6 different strains. Morphological, physiological, and biochemical characterization showed that HBC6-2 strain belongs to the Streptomyces sp. The 16S rRNA sequence of HBC6-2 indicated 99% identity to the corresponding sequence of Streptomyces costaricanus, and was registered on GenBank with the code MT 453944.1. Streptomyces costaricanus EBL.HB6 was able to produce melanin yelow pigment, and its aerial and substrate mycelia have brown and yellow-grey pigment on ISP2, ISP3, ISP4, and ISP5 cultivating medium, respectively. The optimal pH range was from 5-10 and temperature from 15-40°C and exhibited salt tolerance up to 3% and utilized the carbon sources such as fructose, xylose, arabinose, cellulose, and rhamnose. In the following investigation, Streptomyces costaricanus EBL.HB6 displayed the highest α-glucosidase inhibitory activity by 68.98% among Streptomyces sp. strains